“COLOR AS FIELD” WEIGHTLESS & FLOATING FREE - Kumar, Vinay (International Journal of Research -GRANTHAALAYAH, 2014)
“Although the composition and function of colour are two of the most important factors in determining the qualitative content of a painting, the reciprocal relation of colour to colour produces a phenomenon of a more mysterious order. This new phenomenon is psychological. A high sensitivity is necessary in order to expand colour into the sphere of the surreal without losing creative ground. Colour stimulates certain moods in us. It awakens joy or fear in accordance with its configuration. In fact, the whole world, as we experience it visually, comes to us through the mystic realm of colours. Our entire being is nourished by it. This mystic quality of colour should likewise find expression in a work of art”. Hans Hofman. “My canvases are not full because they are full of colours but because colour makes the fullness. The fullness thereof is what I am involved in. it is interesting to me to notice how difficult it is for to take the intense heat and blaze of my colours. If my paintings were empty they could take them with ease”. Barnett Newman.